Aglomeraç\~ao econômica e migraç\~ao: Uma análise para o caso Brasileiro - Pedro Henrique Albuquerque; Bruno de Oliveira Cruz; Carlos Wagner de A. Oliveira; Iury R. dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Interstate migration in Brazil represents almost 40% of total internal migration. This paper investigates the economic causes of interstate migration flow. We apply Crozet's model the interaction of increasing returns and transportation cost on the regional dynamics and migration flow in Brazil. We estimate structural parameters to the Brazilian economy, among other the mark-up and the market power in the modern sector. Using those parameters, the hypothesis of black hole solution is rejected to the Brazilian economy, furthermore the basin of attraction of the main agglomeration has a radius close to 320 km, and this result corroborates Diniz (1995)'s previous analyses of "de-concentration concentrated" in Southeast/South polygon. Expected wage and distance are also relevant for the interstate migration in Brazil, the elasticity of expected wage is significant and varies according to the specification from 0.08 to 0.17 in line with the international literature.
Keywords: F12; R12; R23; 330; migration; regional economics; center-periphery models